Serum soluble receptor for advanced glycation end‐products during acute bronchiolitis in infant: Prospective study in 93 cases. Issue 10 (16th August 2018) - Egron, Carole; Roszyk, Laurence; Rochette, Emmanuelle; Jabaudon, Matthieu; Sapin, Vincent; Mulliez, Aurélien; Labbé, André; Coste, Karen
ABSTRACT: Introduction: Acute bronchiolitis is a major cause of acute respiratory distress in infants. The soluble receptor for advanced glycation end‐products (sRAGE) is a biomarker of pulmonary damage processes, with a diagnostic and a prognostic value in acute respiratory distress syndrome (ARDS). The RAGE pathway is also implicated in the pathogenesis of other respiratory diseases like asthma, but the value of sRAGE levels in acute bronchiolitis remains under‐investigated. Material and methods: A prospective, observational, and analytical study was conducted at Clermont‐Ferrand University Hospital. The main objective was to evaluate the correlation between serum sRAGE and clinical severity of bronchiolitis in hospitalized infants aged <1 year. We analyzed correlations between serum sRAGE and Wainwright score, short‐term morbidity attributable to bronchiolitis, causal viruses and risk for recurrent wheezing at 1 year. Results: The study included 93 infants. sRAGE levels were significantly lower in acute bronchiolitis patients (mean 1101 pg/mL) than in controls (2203 pg/mL, P  < 0.001) but did not correlate with clinical severity. No correlation was found between serum sRAGE and severity score, respiratory viruses, and recurrent wheezing at 1 year. Serum sRAGE levels were negatively correlated with age ( r  = −0.45, P  < 0.001). Conclusion: Serum sRAGE levels are decreased in acute bronchiolitis but not correlated with disease severity. sRAGE levels should be age‐adjusted in infants. Serum sRAGE levels measured in the setting of acute bronchiolitis were not predictive of recurrent wheezing.